Effect Of Human Development Index Fund on Economic Growth Through A Special Autonomy - Irham Iskandar (Muhammadiyah University Press, 2017)
This study aims to determine the human development index on economic growth through the provision of special autonomy. The method used is research development with panel data analysis in 23 districts / cities. The results showed that the moderation between the human development index through special autonomy fund a significant negative effect on economic growth. It indicates the use of special autonomy funds for the human development index is still up, so the future is expected to need to be allocated according to the needs in the region, so that the special autonomy funds can effectively and efficiently.